PEREMPUAN DALAM CITRA KETIDAKADILAN GENDER (Kajian Feminis dan Resepsi atas Kisah Yusuf dalam Serat Yusuf) - Gazali, Hatim; Isma, Muwafiqotul (MUWAZAH, 2016)
In Islam, men and women are equal before God (das sollen). However, stereotype, discrimination and violance against woman often happen everywhere. The position of women according to the Serat Yusuf as a literature that was born from the social construction and the storage author who is gender bias placed women unequally. This research that used philology theory, reception theory and feminism theory examined the picture of unequal gender in Yusuf-Zulaikha in Serat Yusuf. Based on Philology theory, it was found that Serat Yusuf who was written by Nalaputra is a sung text. It was written in 1935 that consist of 29 chapters (pupuh). While based on the reception theory, the study revealed that the reading of Nalaputra as the writer of the Serat Yusuf on YusufZulaikha story that consists in the holy Quran experienced the expansion and additional part, plot, character. In the analysis of the feminist theory, the study discovered forms of unequal position of women such as women are perceived as a passive, emotional, unable to control their desire, men servants and their faith are lower than men.Di dalam Islam, laki-laki dan perempuan adalah sama di hadapan Allah SWT (das sollen). Namun, stereotip, diskriminasi dan kekerasan terhadap perempuan sering terjadi di mana-mana. Posisi perempuan menurut Serat Yusuf sebagai sastra yang lahir dari konstruksi sosial yang bias gender menempatkan perempuan secara tidak setara. Penelitian ini yang menggunakan teori filologi, teori resepsi dan teori feminisme. Berdasarkan teori filologi, ditemukan bahwa Serat Yusuf yang ditulis oleh Nalaputra adalah syair yang ditulis pada tahun 1935, terdiri dari 29 bab (pupuh). Sementara berdasarkan teori resepsi menunjukkan bahwa, pembacaan Nalaputra terhadap Serat Yusuf, kisah Yusuf-Zulaikha mengalami ekspansi dan tambahan pada bagian, plot , karakter yang berbeda dari Al-Quran. Analisis teori feminis, menemukan posisi yang tidak sama dari perempuan seperti perempuan dianggap pasif, emosional, tidak mampu mengendalikan keinginan mereka, makhluk hamba dan iman mereka lebih rendah daripada laki-laki.